PROJECT SCHEDULING WITH CPM AND PERT METHODS ON THE PT. JAKARTA INDUSTRIAL ESTATE PULOGADUNG MOSQUE CONSTRUCTION PROJECT - FAIZAL ADDIN ACHMAD; YONAS PRIMA ARGA RUMBYARSO (CV KULTURA DIGITAL MEDIA, 2024)
Project implementation requires accurate planning, scheduling, and management, covering various aspects such as resources, availability of materials, equipment, natural conditions, weather, and other factors that affect project development. Project planning reflects the relationship between activities and the overall project sequence, and helps in prioritizing the relationship between activities. Various methods are available to analyze project schedules. This research uses the Critical Path Method and Progam Evaluation and Review Technique, which is slightly different from the approach used in the construction of the Mosque at PT Jakarta Industrial Estate Pulogadung. In this study, Microsoft Project software was used for the calculation of CPM and PERT methods. Based on the analysis results, 6 work items were found to be on the critical path, namely: preparatory work, lower structure, upper structure, architecture, hardscape and softscape. The project completion time is estimated to be 105 days with the CPM method and 101 days with the PERT method, with a project completion opportunity of 37.37%.